Effectiveness of Behavior Contract–Based Group Counseling in Reducing Truancy among Junior High School Students - Defri Khoirul Rizki; Akhmad Rudi Masrukhin; Faisol Hakim (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aimed to examine the effectiveness of behavior contract–based group counseling in reducing truancy behavior among junior high school students. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants consisted of 11 seventh-grade students identified through a needs assessment as having high levels of truancy. Data were collected using a validated truancy behavior questionnaire. Data analysis was conducted using the Wilcoxon Signed-Rank Test. The results showed a decrease in the mean truancy score from 66.73 in the pretest to 54.18 in the posttest, with a Z value of −3.059 and a significance level of 0.001 (p < 0.05). These findings indicate that group counseling integrated with behavior contract techniques is effective in reducing truancy behavior. The novelty of this study lies in applying a structured behavioral contract within group counseling in an Islamic junior high school context.